Development of Make a Match-Based Puzzle Media Five Asma'ul Husna Materials and Their Meanings - Nasir, Septian; Taqwa, Taqwa; Nurjaya, Erni (Educational Journal of Learning Technology, 2024)
This research develops a make-a-match-based puzzle learning media for Islamic Religious Education subjects with the material of five Asma'ul Husna in grade IV of SDN 25 Sabbamparu. The research aims to analyze student needs, design, development, practicality, and effectiveness of this learning media. The research uses the R&D method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, involving 21 students and two teachers. The study results showed that the make-a-match-based puzzle media was feasible with the assessment of 69.2% media experts, 97.9% material experts, and 75% linguists. The practicality of the media was considered very high by teachers (96.6%) and students (82.9%). The interpretation of the results shows that this media increases students' interest and enthusiasm for learning and helps them apply Asma'ul Husna. The recommendation is to expand the use of this media in various schools and conduct further research to measure the long-term impact on the character and morale of students.